Kremlin launches risky pension reform: Plan to raise retirement age undermines confidence in Russian leadership - Janis Kluge (Stiftung Wissenschaft und Politik (SWP), 2018)
On 14 June, Prime Minister Dmitry Medvedev announced proposals to gradually raise the retirement age in Russia from 2019. The Russian leadership wants to use this reform to tighten its budget and boost economic growth. Despite the media distraction caused by the Football World Cup, there is growing protest against the proposal. Trade unions, loyal opposition and Alexei Navalny are planning demonstrations. The Kremlin has framed the unpopular reform as a government project that President Putin has nothing to do with. Nevertheless, confidence in the President has been dented. A clear social response could lead to a weakening of the reform and although the Kremlin has many instruments at its disposal to stem the threat of protests, it lacks the means to regain the trust it has lost.
Keywords: 320